Comparison of PCR testing methods for white spot syndrome virus (WSSV) infections in penaeid shrimp - Kallaya Sritunyalucksana (2018)
In Thailand, several PCR-based methods are used by private and public service laboratories for the detection of white spot syndrome virus (WSSV) infection in penaeid shrimp post larvae (PL) before they are stocked in rearing ponds. Conflicting test results for similar samples sent to two service laboratories has decreased confidence in PCR testing. Thus, we compared the sensitivity of several PCR methods commonly employed in Thailand using Taqman real-time PCR as the gold standard with a purified WSSV template stock. Using this stock for assays, we found no significant inhibitory effect by WSSV-free host shrimp DNA over the range 0 to 300 ng per reaction or by added DNA from WSSV-infected shrimp. Real-time PCR could detect WSSV with certainty at dilutions of approximately 5 copies per reaction while 1000 copies were needed for a common one-step PCR method and 50 for a common single-tube nested PCR (1N-PCR) method. Of 2 two-tube nested PCR protocols tested, one required 100 and the other 1000 copies. In addition to these sensitivity tests, a triple-blind ring test was carried out employing sets of 10 WSSV-infected DNA extracts sent to 12 commercial and public laboratories in Thailand, without specifying the PCR method to be used. Returned results included no false positives and two false negatives, the latter both from light infection vials. This translated into a test sensitivity of 97.3% and a specificity of 100%. Overall, the results confirmed the validity of PCR-based methods in Thailand for detection of WSSV in shrimp DNA extracts. © 2005 Elsevier B.V. All rights reserved.